Design and Implementation of Multifunction Relay Based on Microcontroller - Hameed, Ali Abdulsattar; Sultan, Ahmed Jasim; Booneya, Mehdi F. (Journal of Techniques, 2021)
The power systems are exposed to many abnormal conditions, so an advanced protection system must be provided to stand up to these challenges. Protection devices evolved continuously with the development of power systems. The accuracy, high response, reliability, and speed of fault detection are required in the operating mode of multi-function protective relays. A Multifunction Relay has been designed and implemented, which consists of three types of relays: over current relay OCR, over/under voltage relay OVR/UVR, and differential relay DFR. The relays OCR, OVR/UVR, and DFR are designed according to the standards IEC 60255, IEEE 1159, and IEEE C37.91, respectively, based on Arduino MEGA. The multi-function relay was implemented to work on a single phase. The setting of the multi-function relay configuration done using a new design based on the MATLAB GUI environment. Furthermore, the results obtained after each test appear on it and LCD screen. The multi-function relay which is designed can work as (OCR, OVR/UVR, DFR) in the case of a single-phase source. The experiential results show that the proposed multi-function relay is accurate, fast response, reliable, selective, good performance, low cost, and sensitivity when used to protect the power system equipment under different operating conditions.